(untitled) (KULT_online, 2020)
Based on a conference in spring 2017 at the GCSC (International Graduate Centre for the Study of Culture), Justus-Liebig-University Giessen, Germany, the anthology focusses from an interdisciplinary approach on the manifold ways of representation of modern monarchies since the earliest 19th century and the output of literary adaptions and other medial ways of reception. The research focus lies on the European Monarchies, especially the British Monarchy.